2015
DOI: 10.1175/mwr-d-15-0076.1
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Impact of Initialization Shocks in Coupled Atmosphere–Ocean Forecasts*

Abstract: Current methods for initializing coupled atmosphere–ocean forecasts often rely on the use of separate atmosphere and ocean analyses, the combination of which can leave the coupled system imbalanced at the beginning of the forecast, potentially accelerating the development of errors. Using a series of experiments with the European Centre for Medium-Range Weather Forecasts coupled system, the magnitude and extent of these so-called initialization shocks is quantified, and their impact on forecast skill measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 31 publications
0
79
0
Order By: Relevance
“…However, the issue of drift may be tackled successfully by a posteriori bias correction (e.g., Magnusson et al 2012) and the issue of initial shocks is not exclusive to initialization from full-fields. A variety of reasons such as application of independent, uncoupled atmosphere and ocean reanalyses or application of a reanalysis product of poor quality in the assimilation procedure can lead to an imbalanced initial state in the coupled prediction system that triggers initial shocks in the forecasts (e.g., Balmaseda and Anderson 2009;Mulholland et al 2015;Pohlmann et al 2017). In this paper, we investigate how changing our decadal prediction system from anomaly nudging to full-field nudging in the ocean influences our prediction skill for sea surface temperature (SST) and ocean heat content (OHC) in the northern North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the issue of drift may be tackled successfully by a posteriori bias correction (e.g., Magnusson et al 2012) and the issue of initial shocks is not exclusive to initialization from full-fields. A variety of reasons such as application of independent, uncoupled atmosphere and ocean reanalyses or application of a reanalysis product of poor quality in the assimilation procedure can lead to an imbalanced initial state in the coupled prediction system that triggers initial shocks in the forecasts (e.g., Balmaseda and Anderson 2009;Mulholland et al 2015;Pohlmann et al 2017). In this paper, we investigate how changing our decadal prediction system from anomaly nudging to full-field nudging in the ocean influences our prediction skill for sea surface temperature (SST) and ocean heat content (OHC) in the northern North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…One problem encountered when initializing a model from a nonnative starting state is the possibility of an initial shock as the forecast model moves rapidly toward its own attractor (Klocke & Rodwell, ; Mulholland et al, ). We only see evidence suggesting this behavior in humidity forecasts in the SCM, with an initial rapid drying and associated anomalously high precipitation rate over the first hour, which decrease to a stable rate.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Mullholland et al (2015), for example, found that imbalances between the atmosphere and ocean initial conditions could create drifts. Heat fluxes to the ocean component will almost certainly be erroneous in the initial state as during the assimilation phase ocean data increments can compensate for errors in the atmospheric forcing.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Our definition of drift includes changes caused by imperfect initialization, which are sometimes referred to as "shock" (Mullholland et al 2015). We consider the drift in the first four months of the 1 May and 1 November start dates and also the summer (June-August) and winter (December-February) biases.…”
Section: Models Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation